A Multifaceted Strategy to Implement Brief Smoking Cessation Counseling During Antenatal Care in Argentina and Uruguay: A Cluster Randomized Trial - Althabe, Fernando (2016)
Introduction: Argentina and Uruguay have a high prevalence of smoking during pregnancy. However, and despite national recommendations, pregnant women are not routinely receiving cessation counseling during antenatal care (ANC). We evaluated a multifaceted strategy designed to increase the frequency of pregnant women who received a brief smoking cessation counseling based on the 5As (Ask, Advise, Assess, Assist, and Arrange). Methods: We randomly assigned (1:1) 20 ANC clusters in Buenos Aires, Argentina and Montevideo, Uruguay to receive a multifaceted intervention to implement brief smoking cessation counseling into routine ANC, or to receive no intervention. The primary outcome was the frequency of women who recalled receiving the 5As during ANC at more than one visit. Frequency of women who smoked until the end of pregnancy, and attitudes and readiness of ANC providers towards providing counseling were secondary outcomes. Women’s outcomes were measured at baseline and at the end of the 14- to 18-month intervention, by administering questionnaires at the postpartum hospital stay. Self-reported cessation was verified with saliva cotinine. The trial took place between October 03, 2011 and November 29, 2013. Results: The rate of women who recalled receiving the 5As increased from 14.0% to 33.6% in the intervention group (median rate change, 22.1%), and from 10.8% to 17.0% in the control group (median rate change, 4.6%; P = .001 for the difference in change between groups). The effect of the intervention was larger in Argentina than in Uruguay. The proportion of women who continued smoking during pregnancy was unchanged at follow-up in both groups and the relative difference between groups was not statistically significant (ratio of odds ratios 1.16, 95% CI: 0.98–1.37; P = .086). No significant changes were observed in knowledge, attitudes, and self-confidence of ANC providers. Conclusions: The intervention showed a moderate effect in increasing the proportion of women who recalled receiving the 5As, with a third of women receiving counseling in more than one visit. However, the frequency of women who smoked until the end of the pregnancy was not significantly reduced by the intervention. Implications: No implementation trials of smoking cessation interventions for pregnant women have been carried out in Latin American or in middle-income countries where health care systems or capacities may differ. We evaluated a multifaceted strategy designed to increase the frequency of pregnant women who receive brief smoking cessation counseling based on the 5As in Argentina and Uruguay. We found that the intervention showed a moderate effect in increasing the proportion of women receiving the 5As, with a third of women receiving counseling in more than one visit. However, the frequency of women who smoked until the end of the pregnancy was not significantly reduced by the intervention.